Functional parameters of generalized content sentences (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The author analyzes communicative mechanisms, which determine the actualization of generalized content. This content is representatived in language structure. The peculiarities of speech situations which realize generalized content are determined: arbitrary of quantitative structure of participants, multispectral characters of relations between speaker and listener, actuality of speaker's psychological characteristics.
Keywords: communicative stipulation; communicative status; speech situation; generalized content